2020
DOI: 10.22462/01.03.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for COVID-19 patients with respiratory distress: treated cases versus propensity-matched controls

Abstract: Decompression sickness (DCS) occurs when nitrogen gas (N2) comes out of solution too quickly, forming bubbles in the blood and tissues. These bubbles can be a serious condition; thus it is of extreme interest in the dive community to model DCS risk. Diving models use tissue compartments to calculate tissue partial pressures, often using data obtained from other mammalian species (i.e., pigs). Adipose tissue is an important compartment in these models because N2 is five times more soluble in fat than in blood; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“… 22 HBO 2 treatment below 2.0 ATA increases the activity of antioxidant enzymes, including first-line defence antioxidants superoxide dismutase and catalase. 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 22 HBO 2 treatment below 2.0 ATA increases the activity of antioxidant enzymes, including first-line defence antioxidants superoxide dismutase and catalase. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 12–15 However, as the increased pressure of HBO 2 therapy may exacerbate an acute lung injury or induce pulmonary oedema among patients with COVID-19, potential complications must be assessed. 11 The objective of this study was to analyse the safety and efficacy of HBO 2 treatment in patients with COVID-19 with severe hypoxaemia in the reduction of time for recovery from hypoxaemia (defined as SatO 2 ≤93%). Also, the study evaluated if HBO 2 treatment decreased progression to respiratory distress, mechanical ventilation requirements and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the data from this study are consistent with other recent work involving HBO 2 therapy in patients with COVID-19. These studies have shown that patients begin treatment with very high respiratory rates and raised inflammatory markers, both of which seem to decrease with HBO 2 5 6. during and even after HBO therapy periods.…”
mentioning
confidence: 97%